Severe congenital neutropenia‐associated JAGN1 mutations unleash a calpain‐dependent cell death programme in myeloid cells. (18th November 2020) - Khandagale, Avinash; Holmlund, Teresa; Entesarian, Miriam; Nilsson, Daniel; Kalwak, Krzysztof; Klaudel‐Dreszler, Maja; Carlsson, Göran; Henter, Jan‐Inge; Nordenskjöld, Magnus; Fadeel, Bengt
Summary: Severe congenital neutropenia (SCN) of autosomal recessive inheritance, also known as Kostmann disease, is characterised by a lack of neutrophils and a propensity for life‐threatening infections. Using whole‐exome sequencing, we identified homozygous JAGN1 mutations (p.Gly14Ser and p.Glu21Asp) in three patients with Kostmann‐like SCN, thus confirming the recent attribution of JAGN1 mutations to SCN. Using the human promyelocytic cell line HL‐60 as a model, we found that overexpression of patient‐derived JAGN1 mutants, but not silencing of JAGN1, augmented cell death in response to the pro‐apoptotic stimuli, etoposide, staurosporine, and thapsigargin. Furthermore, cells expressing mutant JAGN1 were remarkably susceptible to agonists that normally trigger degranulation and succumbed to a calcium‐dependent cell death programme. This mode of cell death was completely prevented by pharmacological inhibition of calpain but unaffected by caspase inhibition. In conclusion, our results confirmed the association between JAGN1 mutations and SCN and showed that SCN‐associated JAGN1 mutations unleash a calcium‐ and calpain‐dependent cell death in myeloid cells.